Segregation of particles during maize loading process in a center-loaded silo - Guixiang Chen; Chaosai Liu; Deqian Zheng; Dianxuan Wang (Scientific Reports)
Abstract Kernel breakage and segregation are unavoidable phenomena during maize loading process in the silo, and the study of this phenomenon is beneficial for solving the aeration, drying and insect control in grain storage. Distribution and segregation of broken kernels, dust, and fragments (BKDF), inorganic impurities, foreign kernels and other organic impurities were studied by maize loading process in a center-loaded silo. Maize was loaded through a vertical funnel into the silo from four drop heights (0.3, 1, 2 and 3.1 m). Samples were collected using a sampling tube inserted vertically at a Y-shaped locations along three radii of the silo for each drop heights. The difference in porosity distribution in the spatial position of the maize bulk caused by kernel breakage and segregation was determined. Higher drop heights increased the content of BKDF, and the BKDF decreased nonlinearly with the increase of distance from the center of the silo. The foreign kernels concentration near the center of the silo was higher than that near the silo wall. Inorganic impurities mainly accumulated in the 1/4–3/4 radius, while other organic impurities accumulated mostly near the wall of the silo. A nonlinear model considering kernel breakage and segregation was developed to predict the porosity distribution in the vertical and radial direction in the silo. Kernel breakage and segregation minimize the porosity at the center of the silo. The porosity of the silo center was 0.421–0.438, and it increased with the distance from the center of the silo increased.